"TIME-RELEASE" OUTPUT RESPONSES TO PUBLIC EDUCATION EXPENDITURES. (11th January 2021) - Atems, Bebonchu; Blankenau, William
Abstract : This paper argues that output can respond to public education spending in a delayed and persistent manner through human capital accumulation. We refer to this as a "time-release" response, reflecting that the output response grows as students exposed to increased expenditures sequentially enter the labor market. We first develop and calibrate a stochastic overlapping generations model to formalize the propagation of spending shocks over a long time horizon. We then empirically explore this time-release aspect of shocks to government education expenditures on output using US state-level data for the period 1963–2016 and a panel structural vector autoregression methodology. Consistent with the model, our empirical results show that the dynamic response of output to shocks to government education expenditures is positive, significant, and long-lasting.